CdS(en) hybrid nanoparticles supported on Mg(OH)2-MgO mixture. Suitable preparation via a one pot synthesis for the photocatalytic H2 production - Angela Gabriela Romero-Villegas; Sandra Ramírez-Rave; Agileo Hernández-Gordillo; Iván D. Rojas-Montoya; Ricardo Gómez (Journal of Materials Science: Materials in Engineering)
Abstract CdS(en)/Mg(OH)2-MgO photocatalysts were easily synthesized using a one pot synthesis, the resulting materials were obtained with an excellent dispersion of the hybrid CdS(en) on the surface. Their structural, optical, and morphological properties were characterized by X-ray diffraction, UV–vis spectroscopy, FTIR spectroscopy, nitrogen physisorption, and scanning electron microscopy (SEM). These supported materials were used as photocatalysts in the hydrogen evolution reaction (HER), using water as the raw material, and methanol as a sacrificial molecule under visible (blue) light irradiation. CdS(en)/Mg(OH)2-MgO materials presented high performances in the HER reaction. When Mg(OH)2-MgO support was obtained by ammonia pre-treatment of MgO, an improvement in the electronic-optical and textural properties was observed, resulting in an enhancement in the H2 yields. Notably, in comparison to previously reported CdS-supported materials which achieved H2 production rates of 64–300 μmol/gh, the photocatalysts presented in this study exhibit significantly superior performance. Specifically, CS/Mg5H is almost 5 times more active, producing exceptional H2 yields while requiring only a small amount of catalyst (50 mg containing just 4.2 wt.% CdS). Furthermore, this remarkable performance is achieved under visible light irradiation using low-intensity 12 W LED lamps.